أثر مشاركة العميل على نواتج الخدمات المصرفية المقدمة في المصارف التجارية الليبية العامة العاملة في مدينة بنغازي - الكيخيا فيصل سالم; محمد حسن خالد مريم (Scientific Journal of University of Benghazi, 2020)
This research aimed to determine the impact of the customer participation on the banking services outcomes provided by the Public Libyan Commercial Banks operate in Benghazi. To achieve this aim, a survey was used to collect and analyze data, through an intercepted sample consisting of (384) individual customers of the commercial banks in question. To analyze the research data, a set of statistical methods were used for the purposes of analysis and hypothesis testing. The research concluded that the customer participation has a positive moral effect on the banking service outcomes provided by the Public Libyan Commercial Banks operate in Benghazi. The research also found that there is no difference in the levels of customer participation in the process of performing and providing the service according to the customer’s demographic variables (age, educational level, bank name, activity type, account type), the presence of a difference in the levels of customer participation regarding to the variable of the customer type, and the absence of a difference in the banking service outcomes provided to the customers of these banks. In the light of these results, the research presented a set of recommendations that would enhance the awareness of the Public Libyan Commercial Banks of the importance and role of the customer participation in improving the quality of the banking service provided.